A Numerical Simulation of the Martian Polar Cap Breeze - Fernández Rojas, Walter (1995)
A mathematical model for the Martian polar cap breeze was constructed in part from work previously done by others on the terrestrial sea breeze. With this model a numerical simulation corresponding to the Southem Hemisphere winter season was made. The results obtained with the proposed model show that the Martian polar cap breeze is a well defined system with some similarities to the terrestrial sea breeze. At the time of maximum intensity, the largest values of vertical velocities are about 10 cm/s and occur at heights between 850-1250 m. The largest values of horizontal velocities are about 15 m/s. A "polar cap breeze front" is clearly discernible in the results. The rate of advance of this front is at an average of about I0 km/h.